THE RELATIONSHIP BETWEEN KNOWLEDGE, ATTITUDE AND FAMILY SUPPORT AND THE SUCCESS OF EXCLUSIVE BREASTFEEDING - Khadizah Syahputri; Anita Purba; Annur Rusdyah Lubis; Desmawati Zebua; Tiarnida Nababan; Melita Riama Manik (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2025)
Exclusive breastfeeding for the first 6 months of life is an international standard; recommended by WHO and UNICEF to ensure the growth, development, and protection of infants from various infections. The success of exclusive breastfeeding is determined by various aspects, such as maternal knowledge, attitudes, family support, and social environmental conditions. This study aims to evaluate the level of success in exclusive breastfeeding practices. This research applies a quantitative method with a descriptive analytical design and a cross-sectional method. The population consists of mothers with babies aged 0-6 months, with a sample size of 30 people, using the total sampling method. The statistical analysis applied was the chi-square test to identify significant relationships between variables, with a significance limit of ɑ = 0.05. The results of the study showed that 43.3% of respondents had good knowledge about exclusive breastfeeding, 66.7% had a positive attitude, 63.3% received family support, and 73.3% had a successful rate of exclusive breastfeeding. The chi-square test showed a significant relationship between attitudes (P=0.045), knowledge (P=0.004), and family support showed stronger significance (P=0.001).